Prediction of collapse load and design of reinforced single - cell concrete box-girder bridges using truss models - Chithra, J.; Nagarajan, Praveen; Sajith, A.S. (Journal of Structural Engineering, 2024)
Box girder bridges are always a designer’s favourite due to many of their advantages. Several research works are goingon in this area to identify the behaviour of the box sections when subjected to different types of loading and analyses.Collapse load prediction in box girder bridges is one among them. The elastic behaviour of these kinds of structures canbe predicted easily, but to understand their post cracking behaviour, either three-dimensional non-linear finite elementanalyses or experiments conducted on scaled-down models are required. It is also found that many simplified modelsare available to study the behaviour of single-cell box girder bridges. However, they cannot be used to understandtheir non-linear behaviour completely. Among the simplified methods, collapse mechanism and space truss analogyare the two methods with which the ultimate load of such a structure can be estimated. In this paper, the collapseload prediction is attempted using plane truss analogy, space truss analogy and numerical study. The results are thencompared. The design of a full-scale box girder bridge using a space truss model is also presented in the paper.